HUBUNGAN ANTARA FUNGSI KOGNITIF DAN KETERAMPILAN MOTORIK KASAR PADA ANAK DOWN SYNDROME DI YPLB NUSANTARA DEPOK - Bunga Anisa (2023)
Background: Children with Down syndrome have a higher risk of health problems than normal children in general. Caused, the Down Syndrome is a disorder in a person caused by the imperfections in the formation of chromosomes. This imperfection of chromosome formation causes cognitive function disorders and the development of gross motor skills during the child's growth period. Research Purposes: To determine the correlation between cognitive function and gross motor skills in children with Down syndrome. Methods: This study used a correlational quantitative research design with a cross-sectional approach. With a sample of 83 children with Down syndrome and with an error rate of 5%. This research was carried out offline and using the Cognitive Scale for Down Syndrome (CS-DS) and Gross Motor Function Measuring (GMFM) as the measuring instrument. Result Researchs : The results obtained in this study are that there is a significant relationship between cognitive function and gross motor skills in children with Down syndrome with a value of P = 0.000 for both variables and a correlation coefficient of r = 1.000 for cognitive function and r = 0.463 for gross motor skills . Because the value of r is positive for both variables, the relationship between the two variables is unidirectional. Conclusion Researchs : The resulted that there was a relationship between cognitive function and gross motor skills in the same direction in children with Down syndrome at YPLB Nusantara Depok